Understanding emotion regulation strategies in female adolescents with depressive symptoms: a qualitative study - Yusoff, Siti Rashidah; Khairuddin, Khairul Farhah; Mohd Hoesni, Suzana; Rosharudin, Nur Afrina; Mohd Daud, Tuti Iryani; Muhammad, Noor Azimah; Mohd Ali, Manisah; Razman, Mohamad Omar Ihsan; Mohd Kari, Dharatun Nissa Puad; Abdullah, Mohd Pilus (International Journal of Evaluation and Research in Education (IJERE), 2025)
In Malaysia, adolescents are at a high risk for depression, with the prevalence rising from 18.3% in 2017 to 26.9% in 2022. Additionally, the proportion of female adolescents affected is significantly higher than male adolescents, with 36.1% of females experiencing depression compared to 17.7% of males. Thus, a qualitative study was conducted to explore the emotion regulation strategies used by female adolescents experiencing depressive symptoms. Semi-structured interviews were performed with 15 female adolescents, aged 14 to 16 years, who had severe depression scores as assessed by the DASS-21. Using purposive sampling, all 15 female adolescents were selected from six public secondary schools in the Klang Valley, Malaysia. The Klang Valley, which includes the two main states of Selangor and Kuala Lumpur, was chosen due to its ranking among the top three states in 2022 with the highest rates of depression symptoms. All responses were recorded and analyzed using a thematic analysis approach. The findings revealed that female adolescents employed five emotion regulation strategies: suppressing expression, pampering themselves, seeking support, reorganizing their thoughts, and engaging in negative actions. This study explores the emotional experiences of female adolescents to design feasible and flexible interventions that address a wide range of individual needs.